Mixed crystal defect resistant single-crystal high-temperature alloy material for additive manufacturing and preparation method of mixed crystal defect resistant single-crystal high-temperature alloy material
Through the design of nickel -based single -crystal high -temperature alloy materials for anti -hybrid crystal defects, controlling γ ′ phase to form the element content and bias coefficients, solve the problem of miscellaneous crystal formation in additive manufacturing, and improve the high temperature mechanical performance and process performance of alloy.
Patent Information
- Application Number
- CN202310907878.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-24
AI Technical Summary
In the process of additive manufacturing of single crystal high-temperature alloys, hybrid crystals are easily formed, resulting in the scrapping of components.
A nickel -based single -crystal high -temperature alloy material with anti -hybrid crystal defects includes elements such as C, CR, CO, W, MO, TA, AL, RU, RU, and HF. The formation element content and bias coefficient are reduced to reduce the tendency of the formation of miscellaneous crystals.
It effectively reduces the formation of miscellaneous crystals, improves the high-temperature mechanical properties and process performance of the alloy, and makes it easier to prepare single-crystal structural parts during the additive manufacturing process.
Smart Images

Figure HDA0004354094650000011 
Figure HDA0004354094650000012 
Figure HDA0004354094650000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nickel-based high-temperature alloys, and specifically to a single crystal high-temperature alloy material for additive manufacturing that is resistant to impurity crystal defects and a preparation method thereof. The alloy has the characteristics of high strength and ease of additive manufacturing, as well as good organizational stability, and is particularly suitable for additive manufacturing of high-temperature components in the fields of aerospace, aviation, ships, petrochemicals, etc. Background Art
[0002] Nickel-based high-temperature alloys are key materials for high-temperature structural parts of advanced aerospace engines. With the improvement of the economic benefits of air transportation, high-temperature alloy structural parts are becoming increasingly complex, which is difficult to achieve with traditional casting. Additive manufacturing combines computer-aided design, material processing and molding technology, and is based on digital model files. Through software and CNC systems, special metal materials are deposited layer by layer through high-energy beams such as lasers, electron beams or arcs. Compared with traditional casting methods, the manufacture of complex structural parts that can be achieved by additive manufacturing becomes possible. However, since high-temperature alloys contain a large amount of elements such as Al and Ti, the formation of impurities ( Picture 1-2 ), the formation of impurity crystals is the main factor leading to component scrapping.
[0003] Based on the above background, it is expected to obtain a single crystal high temperature alloy material for additive manufacturing that is resistant to impurity crystal defects and a preparation method. Summary of the invention
[0004] The object of the present invention is to provide a single crystal high-temperature alloy material for additive manufacturing that is resistant to impurity crystal defects and a preparation method thereof. While obtaining higher high-temperature alloy properties, the alloy has the ability to effectively reduce the tendency of impurity crystal formation during the additive manufacturing process, that is, better processability.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A single crystal high temperature alloy material for additive manufacturing resistant to impurity crystal defects, the chemical composition of the alloy is as follows by weight percentage:
[0007] A single crystal high temperature alloy material for additive manufacturing resistant to impurity crystal defects, the chemical composition of the alloy is as follows by weight percentage:
[0008] C 0.06~0.18%, Cr 6.0~8.0%, Co 10~13%, W 3~5%, Mo 1.0~2.0%, Ta 5.5~7.0%, Al 5.0~6.2%, Re 0~1.5%, Ru 0~3%, Hf 1.0~1.6%, and Ni is the balance.
[0009] In the high-temperature alloy material, the weight percentage content of the strengthening phase γ′ phase forming elements Al, Ta and Hf is limited to: 12.0wt.%≤Al+Ta+Hf≤14.0wt.%, and 0.9≤Al / Ta≤1.1, 3.5≤Al / Hf≤4.5, so as to ensure that the alloy has a higher γ′ phase content, so that the alloy has higher high-temperature mechanical properties. In addition, these elements are easy to segregate in the liquid phase (K<1) during the solidification process, which aggravates the supercooling of the liquid phase components and easily leads to the formation of impurity crystals.
[0010] In the high-temperature alloy material, the content of the element with a segregation coefficient K≈1 is increased (for example, the content of Cr, Co and Ru can be increased), and the element with K≈1 is used to adjust the segregation behavior of other elements.
[0011] Preferably, the contents of Cr, Co and Ru in the alloy are controlled to be: 19.0wt.%≤Cr+Co+Ru.
[0012] Segregation coefficient K = |1-K0|, K0 is the distribution coefficient of the solute element. The distribution coefficients of each element in different alloys are different, so the degree of dendrite segregation is also different. The smaller the distribution coefficient K0 (when K0<1) or the larger K0, the more severe the dendrite segregation. Therefore, the segregation coefficient K can be used to qualitatively measure the degree of dendrite segregation. The larger the segregation coefficient K, the more severe the dendrite segregation.
[0013] In the high-temperature alloy material, a large amount of elements with a segregation coefficient K>1 are added to promote the segregation of elements such as Cr, Co and Ru to the liquid phase, so as to reduce the segregation of elements such as Al, Ta and Hf.
[0014] Preferably, the contents of W, Mo and Re in the alloy are controlled to be: 10.0wt.%≤W+Mo+Re≤11.0wt.%.
[0015] The preparation method of the single crystal high temperature alloy material for additive manufacturing resistant to impurity crystal defects is to mix the alloy ingots according to the alloy composition and then perform heat treatment; the heat treatment system is a stress relief treatment temperature of 20-40°C above the γ′ phase dissolution temperature for 1-4 hours to inhibit the alloy from recrystallizing and to apply compressive stress to the alloy to inhibit cracking, and the stress value is ±20MPa of the yield strength of the alloy at this temperature.
[0016] A master alloy ingot is prepared according to the above alloy composition, processed into a rod for argon atomization, and atomized and powdered in an argon atomization furnace; then an additive manufacturing method is used to prepare a single crystal structural part, and finally a hot isostatic pressing treatment is performed.
[0017] The hot isostatic pressing treatment temperature is 20-40°C above the γ′ phase dissolution temperature, and the time is 1-4h to inhibit the alloy from recrystallizing. At the same time, pressure is applied to the alloy to inhibit cracking. The pressure value is the yield strength of the alloy at the hot isostatic pressing treatment temperature ±20MPa.
[0018] The chemical composition design principle of the alloy of the present invention is as follows:
[0019] 1. The nickel-based high-temperature alloy of the present invention is composed of a matrix γ phase, a strengthening phase γ′ phase and a carbide phase, wherein the volume fraction of the strengthening phase γ′ phase is 55% to 65%.
[0020] Al, Ta and Hf are all γ' phase-forming elements, which determine the number of strengthening phases in the alloy and the strengthening effect. By adding relatively large amounts of aluminum, Ta and hafnium elements (12.0wt.%≤Al+Ta+Hf≤14.0wt.%) and limiting 0.9≤Al / Ta≤1.1, 3.5≤Al / Hf≤4.5, a high volume fraction of γ' phase is formed to improve its strength; at the same time, the addition of a specific amount of Hf element can effectively improve the strength of the small-angle grain boundaries of single crystal high-temperature alloys, and under the premise of ensuring that the alloy has a high initial melting temperature, it can reduce the tendency of single crystal hot crack formation in additive manufacturing, so that it has a higher content of process performance strengthening phase γ' phase forming elements.
[0021] The role of Cr in nickel-based high-temperature alloys is to increase the ability to resist oxidation, corrosion and solid solution strengthening. When the alloy contains more strengthening elements such as W and Mo, too high Cr will reduce the structural stability of the alloy and cause the precipitation of topological close-packed phase (TCP). However, the alloy contains only a small amount of Mo, and the Cr content can be increased to improve the performance. In addition, in additive manufacturing alloys, the addition of Cr can significantly reduce the residual stress caused by the rapid precipitation of the γ′ phase of the alloy, so the Cr content in the present invention is 6.0-8.0%.
[0022] The formation of impurity crystals in the additive process is closely related to the degree of supercooling. During the solidification of the alloy, the segregation of the alloy components is prone to form a large degree of supercooling in the liquid phase, leading to the formation of impurity crystals. Therefore, in order to improve the alloy's ability to resist the formation of impurity crystals, it is necessary to reasonably control the segregation of alloy elements during solidification. The content of elements Cr, Co and Ru with a segregation coefficient K≈1 during solidification can be increased, and elements such as K≈1 can be used to adjust the segregation behavior of other elements, so the limit is: 19.0wt.%≤Cr+Co+Ru.
[0023] For W, Mo and Re elements with segregation coefficient K>1 during solidification, they segregate in the solid phase, aggravating the supercooling of the liquid phase components and easily leading to the formation of impurity crystals. A large amount of elements with K>1 can be added to promote the segregation of elements such as Cr, Co and Ru to the liquid phase to reduce the content of Al, Ta and Hf. Therefore, the limit is: 10.0wt.%≤W+Mo+Re≤11.0wt.%.
[0024] The present invention has the following advantages and beneficial effects:
[0025] 1. The density of the alloy of the present invention is 8.4 g / cm 3 ~8.7g / cm 3 .
[0026] 2. Compared with traditional alloys, the alloy of the present invention is easier to prepare single crystals using additive manufacturing methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Picture 1 The tendency of impurity crystal formation in additive manufacturing of traditional single crystal alloys.
[0028] Picture 2 Additive manufacturing of heterocrystalline morphology for traditional DD5 single crystal alloy.
[0029] Picture 3 This is the organizational morphology of the single crystal alloy additive manufacturing of the present invention. DETAILED DESCRIPTION
[0030] The present invention is described in detail below through the accompanying drawings and embodiments.
[0031] Example 1
[0032] The alloy composition of this embodiment is shown in Table 1.
[0033] Table 1 Alloy composition of Example 1 (wt.%)
[0034] C Cr Co W Mo Ta Al Re Ru Hf Ni 0.06 6 10 3 1 5.5 5.5 0 0 1 The rest
[0035] In this embodiment, the master alloy is melted in a vacuum induction furnace, and after conventional batching and vacuum induction melting according to the alloy composition, it is cast into a master alloy ingot with a size of φ80×500mm, and then polished to remove the oxide scale and cut into suitable blocks for atomization powder making.
[0036] The alloy powder is spherical powder, and there is a small amount of satellite powder on the surface of the powder. The powder particle size is between 30μm and 220μm, the average powder particle size is 103μm, and the powder particle size is measured by Bettersize2600 laser particle size distribution instrument (wet method). The single crystal substrate selected for additive manufacturing is DD5 alloy, and the laser additive manufacturing uses CO2 laser, and the powder feeder is protected by argon. The laser forming process parameters are laser power 2100W, spot diameter 2mm, and scanning speed 1000mm / min. The formed nickel-based high-temperature alloy is subjected to hot isostatic pressing treatment, the temperature is 20-40℃ above the γ′ phase dissolution temperature, the time is 1-4h, and the processing pressure is the yield strength of the alloy at this temperature ±20MPa.
[0037] The density of the high-temperature alloy structure prepared in this embodiment is 8.6 g / cm 3 The microstructure of the prepared single crystal alloy additive manufacturing is as follows Picture 3 It can be seen that the additive manufacturing organization effectively reduces the formation of impurity crystals. At the same time, the additive manufacturing structure of this embodiment has obtained higher high-temperature alloy performance, and its endurance life under the test conditions of 1050℃ and 240MPa is more than 50 hours.
[0038] Example 2
[0039] The alloy composition of this embodiment is shown in Table 2.
[0040] Table 2 Example 2 alloy composition (wt.%)
[0041] C Cr Co W Mo Ta Al Re Ru Hf Ni 0.18 8 13 5 2 7 6.2 1.5 3 1.6 The rest
[0042] In this embodiment, the master alloy is melted in a vacuum induction furnace, and after conventional batching and vacuum induction melting according to the alloy composition, it is cast into a master alloy ingot with a size of φ80×500mm, and then polished to remove the oxide scale and cut into suitable blocks for atomization powder making.
[0043] The alloy powder is spherical powder, and there is a small amount of satellite powder on the powder surface. The powder particle size is between 30μm and 220μm, the average powder particle size is 100μm, and the powder particle size is measured by Bettersize2600 laser particle size distribution instrument (wet method). The single crystal substrate selected for additive manufacturing is DD5 alloy, and the laser additive manufacturing uses CO2 laser, and the powder feeder is protected by argon gas. The laser forming process parameters are laser power 2000W, spot diameter 1.5mm, and scanning speed 800mm / min. The formed nickel-based high-temperature alloy is subjected to hot isostatic pressing treatment, and the treatment temperature is 20-40℃ above the γ′ phase dissolution temperature, and the time is 1-4h to inhibit the recrystallization of the alloy. At the same time, in order to inhibit the cracking of the alloy, pressure is applied to the alloy, and the pressure value is the yield strength of the alloy at this temperature ±20MPa.
[0044] The density of the high-temperature alloy structure prepared in this embodiment is 8.5 g / cm 3 The prepared single crystal alloy additive manufacturing organization effectively reduced the formation of impurity crystals, and its endurance life under the test conditions of 1050℃ and 240MPa was more than 50 hours.
[0045] Example 3
[0046] The alloy composition of this embodiment is shown in Table 3.
[0047] Table 3 Alloy composition of Example 2 (wt.%)
[0048] C Cr Co W Mo Ta Al Re Ru Hf Ni 0.12 7 12 4 1.5 6 5.8 1.0 1.5 1.2 The rest
[0049] In this embodiment, the master alloy is melted in a vacuum induction furnace, and after conventional batching and vacuum induction melting according to the alloy composition, it is cast into a master alloy ingot with a size of φ80×500mm, and then polished to remove the oxide scale and cut into suitable blocks for atomization powder making.
[0050] The alloy powder is spherical powder, and there is a small amount of satellite powder on the surface of the powder. The powder particle size is between 30μm and 220μm, the average powder particle size is 105μm, and the powder particle size is measured by Bettersize2600 laser particle size distribution instrument (wet method). The single crystal substrate selected for additive manufacturing is DD5 alloy, and the laser additive manufacturing uses CO2 laser, and the powder feeder is protected by argon. The laser forming process parameters are laser power 2000W, spot diameter 1.5mm, and scanning speed 800mm / min. The formed nickel-based high-temperature alloy is subjected to hot isostatic pressing treatment, the temperature is 20-40℃ above the γ′ phase dissolution temperature, and the time is 1-4h to inhibit the recrystallization of the alloy. At the same time, in order to inhibit the cracking of the alloy, pressure is applied to the alloy, and the pressure value is the yield strength of the alloy at this temperature ±20MPa.
[0051] The density of the high-temperature alloy structure prepared in this embodiment is 8.45 g / cm 3 The additive manufacturing organization effectively reduces the formation of impurity crystals. At the same time, the additive manufacturing structure of this embodiment obtains higher high-temperature alloy performance, and its endurance life under the test conditions of 1050°C and 240MPa is more than 50 hours.
Claims
1. A single crystal high temperature alloy material for additive manufacturing resistant to impurity crystal defects, characterized in that: The chemical composition of the alloy is as follows by weight percentage: C 0.06~0.18%, Cr 6.0~8.0%, Co 10~13%, W 3~5%, Mo 1.0~2.0%, Ta 5.5~7.0%, Al 5.0~6.2%, Re 0~1.5%, Ru 0~3%, Hf 1.0~1.6%, and Ni is the balance.
2. The single crystal high temperature alloy material for additive manufacturing with resistance to impurity crystal defects according to claim 1, characterized in that: In the high-temperature alloy material, the weight percentage content of the strengthening phase γ′ phase forming elements Al, Ta and Hf is limited to: 12.0wt.%≤Al+Ta+Hf≤14.0wt.%, and 0.9≤Al / Ta≤1.1, 3.5≤Al / Hf≤4.5, so as to ensure that the alloy has a higher γ′ phase content, so that the alloy has higher high-temperature mechanical properties. In addition, these elements are easy to segregate in the liquid phase (K<1) during the solidification process, which aggravates the supercooling of the liquid phase components and easily leads to the formation of impurity crystals.
3. The single crystal high temperature alloy material for additive manufacturing with resistance to impurity crystal defects according to claim 1, characterized in that: In order to improve the alloy's ability to resist the formation of impurity crystals, it is necessary to reasonably control the segregation of alloy elements during solidification. During solidification, the content of elements with a segregation coefficient K≈1 is increased (such as the content of Cr, Co and Ru can be increased), and elements with K≈1 are used to adjust the segregation behavior of other elements; where: segregation coefficient K=|1-K0|, K0 is the distribution coefficient of the solute element.
4. The single crystal high temperature alloy material for additive manufacturing with resistance to impurity crystal defects according to claim 1 or 3, characterized in that: In the chemical composition of the single crystal high temperature alloy material, the contents of Cr, Co and Ru are controlled to be: 19.0wt.%≤Cr+Co+Ru.
5. The single crystal high temperature alloy material for additive manufacturing with resistance to impurity crystal defects according to claim 1, characterized in that: During the solidification process, W, Mo and Re elements with a segregation coefficient K>1 segregate in the solid phase, aggravating the supercooling of the liquid phase and easily leading to the formation of impurity crystals. By adding a large amount of elements with K>1, the segregation of elements such as Cr, Co and Ru to the liquid phase can be promoted to reduce the segregation of elements such as Al, Ta and Hf.
6. The single crystal high temperature alloy material for additive manufacturing with resistance to impurity crystal defects according to claim 1 or 5, characterized in that: In the chemical composition of the single crystal high temperature alloy material, the contents of W, Mo and Re are controlled to be: 10.0wt.%≤W+Mo+Re≤11.0wt.%.
7. The method for preparing a single crystal high temperature alloy material for additive manufacturing with resistance to impurity crystal defects according to claim 1, characterized in that: The method first prepares a master alloy ingot, processes it into a rod for argon atomization, and performs atomization and powdering in an argon atomization furnace; then an additive manufacturing method is used to prepare a single crystal structural part, and finally a hot isostatic pressing treatment is performed.
8. The method for preparing a single crystal high temperature alloy material for additive manufacturing with resistance to impurity crystal defects according to claim 7, characterized in that: The hot isostatic pressing treatment temperature is 20-40°C above the γ′ phase dissolution temperature, and the time is 1-4h to inhibit the alloy from recrystallizing. At the same time, stress is applied to the alloy to inhibit cracking. The pressure value is the yield strength of the alloy at the treatment temperature ±20MPa.
Citation Information
Cited By
Powder solder, preparation method and welding method of additive manufacturing high-temperature alloy
CN120095407A